How to treat patients with ST-elevation acute myocardial infarction and multi-vessel disease? - Widimsky, Petr; Holmes, David R (European heart journal, 2011)
Over 50% of ST-segment elevation myocardial infarction (STEMI) patients suffer multi-vessel coronary artery disease, which is known to be associated with worse prognosis. Treatment strategies used in clinical practice vary from acute multi-vessel percutaneous coronary intervention (PCI), through staged PCI procedures to a conservative approach with primary PCI of only the infarct-related artery (IRA) and subsequent medical therapy unless recurrent ischaemia occurs. Each approach has advantages and disadvantages. This review paper summarizes the international experience and authors' opinion on this clinically important question. Multi-vessel disease in STEMI is not a single entity and thus the treatment approach should be individualized. However, the following general rules can be proposed till future large randomized trials prove otherwise: (i) Single-vessel acute PCI should be the default strategy (to treat only the IRA during the acute phase of STEMI). (ii) Acute multi-vessel PCI can be justified only in exceptional patients with multiple critical (>90%) and potentially unstable lesions. (iii) Significant lesions of the non-infarct arteries should be treated either medically or by staged revascularization procedures-both options are currently acceptable.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; balónková koronární angioplastika; zátěžový test; Kaplan-Meier Estimate; Angioplasty, Balloon, Coronary; Exercise Test; Hospital Mortality; výsledek terapie; Kaplanův-Meierův odhad; Coronary Artery Bypass; Humans; lidé; koronární bypass; infarkt myokardu; mortalita v nemocnicích; Myocardial Infarction; Treatment Outcome